Thrombin Elaboration in Endotoxin-Induced intravascular Fibrin Deposition - Lipinski, Boguslaw; Gurewich, Victor; Hyde, Elisabeth (Thrombosis and Haemostasis, 1976)
Intravascular coagulation was induced by two appropriately spaced doses of endotoxin and by infusion of thromboplastin. The resulting fibrin deposition was measured by a previously described quantitative technique. Evidence of thrombin elaboration was obtained indirectly by measurement of fibrin monomer (FM) and by the detection and isolation of a thrombin-induced anticlotting activity. Venous segments were isolated at intervals and examined for thrombus formation following 40 minutes of stasis. Endotoxin triggered thrombin elaboration was not detectable in the circulation for at least one hour and was not accompanied by any thrombosis in isolated venous segments. No thrombin elaboration was found in leukopenic rabbits given endotoxin. In the thromboplastin infused animals, the quantity of fibrin deposited in the organs was comparable to that found after endotoxin. However, thrombin was found in the blood immediately and was associated with thrombosis in the isolatet venous segments. Less thrombin-induced anticoagulant activity was found after thromboplastin than after endotoxin. The findings suggest that endotoxin-induced intravascular coagulation is probably not caused by a mechanism of systemic hypercoagulability due to the release of thromboplastic material into the blood stream. A focal process of thrombin elaboration involving leukocytes is postulated. The study is believed relevant to patients with disseminated intravascular coagulation in whom venous thromboembolism is rarely found despite evidence of extensive microvascular fibrin deposition.